The effects of high intensity interval and moderate intensity aerobic continuous training on some of the glycemic control variables and fetuin-A in type 2 diabetic patients - Meysam Torabi; Bahman Mirzaei (Shahid Beheshti University, 2022)
Background and Purpose: Regular exercise is one of the strongest modulators of type-2 diabetes and most of its effects on cells are caused by changes in cytokines. Fetuin A, as a hepatokine, with known effects on carbohydrate metabolism, is affected by exercise and possibly its intensity in healthy individuals. The aim of this study was to compare the two protocols of high intensity interval and moderate intensity continuous training on some glycemic control variables and plasma levels of fetuin A in patients with type-2 diabetes.Material and Methods: 45 men with type-2 diabetes (age and BMI, respectively, 45.9 ± 4.2 years, and 30.5 ± 2.5 kg / m2) were randomly divided into three groups: control, high intensity interval training (HIIT) and moderate intensity continuous training (MICT). The HIIT protocol includes of four intervals of 4-minute activity with 85 to 95% reserve heart rate, separated by 3-minute active rest. The MICT group also did exercise for 47 minutes with 60 to 70% reserve heart rate.Results: FBS and fetuin A was significantly decreased in both HIIT and MICT groups (P < 0.05) and there was no significant difference between two groups. Similarly, HOMA-IR and plasma insulin levels was decreased significantly in both HIIT and MICT groups (P < 0.05) and the reduction of these two factors in the HIIT group was greater than the MICT group (P < 0.05).Conclusion: Based on the results, both HIIT and MICT can possibly lead to better control of glycemic control and also reduce plasma levels of fetuin A, which seems to be a favorable event due to its initial increase in patients with type 2 diabetes. However, this study did not find a difference between the two types of exercise in reducing fetuin A.